Structural and optoelectronic properties of LiYP (Y = Ca, Mg, and Zn) half-Heusler alloy under pressure: A DFT study - Miri, Mohammed; Ziat, Younes; Belkhanchi, Hamza; Zarhri, Zakaryaa; Ait El Kadi, Youssef (Physica. B, Condensed matter, 2023)
By adjusting the lattice geometry through pressure engineering, it is possible to further enhance and customize various properties of materials even at zero pressure. The utilization of pressure allows for the modification of the electronic structure of materials, presenting a relatively new approach to creating essential features for advanced technological applications. These intriguing applications have served as the driving force behind this research, which investigates the behavior of the LiYP (Y = Ca, Mg, and Zn) Half-Heusler (HH) semiconductor. We shed light on the effects of pressure on the optoelectronic and structural characteristics of LiYP (Y = Ca, Mg, and Zn) using the DFT-based Wien2K code. HHs belong to the F 4‾ 3 m space group (No. 216) and are denoted by the chemical symbol XYZ. The calculations were performed by fitting the computed total energy and atomic volume to the Murnaghan equation of state, allowing us to obtain the bulk modulus, first derivatives, and lattice constant. Through the analysis of the partial density of states (PDOS), we evaluated the electronic band structure of LiYP (Y = Ca, Mg, and Zn) under pressures ranging from 0 to 10 GPa. Finally, we examined the optical properties of LiYP and relevant parameters (real part, imaginary part, absorption coefficient and reflectivity coefficient) at different pressure levels. The results obtained from the analysis of optoelectronic properties demonstrate that LiYP (Y = Ca, Mg, and Zn) is suitable for applications in renewable energy devices. •LiZnP exhibits higher compressibility compared to LiMgP and LiCaP materials.•The imaginary part of the dielectric increases under the effect of pressure and shifts towards higher energy values, except for LiCaP.•LiMgP exbibits favorable absorption values in the ultraviolet range.